Kepemimpinan Transformasional - Putri Handayani; Tia Astaivada; Nia Aisyah; Mochammad Isa Anshori (Universitas Katolik Widya Karya Malang, 2023)
This article aims to describe the concept of transformative leadership in organizations or companies. This article uses a qualitative descriptive approach with a library research method. The results of this article explain overall about transformational leadership which includes understanding, principles, styles, various factors, characteristics, steps, advantages and disadvantages of transformational leadership. The conclusion obtained in this article is that leadership with a new approach is an inevitable need in facing the demands of the times that are so fast. One of them is the need for a transformative leadership model that is able to develop the potential of themselves and their subordinates innovatively, empowering staff and organizations with changes in thinking, developing vision, understanding and understanding of organizational goals, and bringing the organization towardssustainable change.